Downregulation of CIP2A inhibits cancer cell proliferation and vascularization in renal clear cell carcinoma - Gao, Hui; Li, Yuqiao; Lin, Tao; Cheng, Yan; Ma, Yunbo (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2020)
BACKGROUND: CIP2A has been proved to play a role as an oncogene in various types of malignancies while its functionality in renal clear cell carcinoma has not been investigated. Our study aimed to investigate the role of CIP2A in renal clear cell carcinoma and to explore the possible mechanisms. METHODS: A total of 80 patients with renal clear cell carcinoma and 32 healthy people were included in the study. Expression of CIP2A was detected by qRT-PCR. CIP2A silencing renal clear cell carcinoma cell line was established. Its effects on cell proliferation and migration were verified by CCK-8 assay and Transwell cell assay, respectively. The effects of CIP2A overexpression on AKT and VEGF were investigated. RESULTS: CIP2A expression level was increased in tumor tissues compared to adjacent healthy tissues. Serum levels of CIP2A protein were higher in cancer patients than in healthy controls, and serum levels of CIP2A protein were increased with increased stage of primary tumor. Serum CIP2A protein can be used to accurately predict renal clear cell carcinoma and its prognosis. CIP2A siRNA silencing inhibited tumor cell proliferation, and treatment with Akt activator reduced this inhibitory effect. CIP2A siRNA silencing decreased the expression level of VEGF and phosphorylation levels of AKT in renal clear cell carcinoma cells, while AKT activator treatment showed no significant effects on CIP2A expression. CONCLUSION: Downregulation of CIP2A can inhibit cancer cell proliferation and vascularization in renal clear cell carcinoma through inactivation of the Akt pathway and its downstream VEGF.
Keywords: senioři; membránové proteiny; nádorové buněčné linie; Carcinoma, Renal Cell; Cell Movement; renal clear cell carcinoma; Membrane Proteins; vaskulární endoteliální růstový faktor A; Male; CIP2A; Proto-Oncogene Proteins c-akt; lidé; Autoantigens; Middle Aged; mužské pohlaví; studie případů a kontrol; karcinom z renálních buněk; Cell Proliferation; Adult; mladý dospělý; Cell Line, Tumor; Intracellular Signaling Peptides and Proteins; Kidney Neoplasms; Gene Knockdown Techniques; protoonkogenní proteiny c-akt; Young Adult; ženské pohlaví; intracelulární signální peptidy a proteiny; Humans; pohyb buněk; patologická angiogeneze; autoantigeny; AKT; lidé středního věku; genový knockdown; Neovascularization, Pathologic; VEGF; Vascular Endothelial Growth Factor A; proliferace buněk; dospělí; Female; Aged; nádory ledvin; Case-Control Studies